2011
DOI: 10.1111/j.1464-410x.2011.10202.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the PCA3 assay in predicting prostate biopsy outcome in a South African setting

Abstract: Study Type – Diagnostic (exploratory cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? The PCA3 assay has shown significant potential amongst the initial studies carried out in Western countries. This assay performed in line with previous studies. We have shown this marker to perform independent of prostatic volume and have identified potential indications for its use in our setting. However, we have not observed the PCA3 assay to outperform the PSA level across the risk sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
(23 reference statements)
0
18
1
2
Order By: Relevance
“…However, 12 additional studies included matched results of PCA3 and the comparators but enrolled men with both initial and repeat biopsies or they did not report biopsy history. 10,11,[35][36][37][38][39][40][41][42][43][44] Most often, the results from these studies were not stratified by biopsy history.…”
Section: Clinical Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, 12 additional studies included matched results of PCA3 and the comparators but enrolled men with both initial and repeat biopsies or they did not report biopsy history. 10,11,[35][36][37][38][39][40][41][42][43][44] Most often, the results from these studies were not stratified by biopsy history.…”
Section: Clinical Validitymentioning
confidence: 99%
“…Fifteen studies [9][10][11]30,32,[34][35][36][37][38][39][40][41][42][43]46 reported AUC estimates for tPSA and PCA3 in the same population. Overall, 13 [9][10][11]30,32,34,35,37,38,[40][41][42]46 of the15 studies found that the AUC of PCA3 was higher than that of tPSA.…”
Section: Clinical Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Une explication réside d'ailleurs dans le fait que l'affirmation d'une HBP reste toujours difficile sur le seul examen histologique de biopsies prostatiques. Certains auteurs ont parfois précisé que des patients avec HBP avaient été inclus [8,10,48] et ont considéré d'emblée que le score PCA3 dans cette population ne devait pas être différent de celui du groupe de patients avec prostate normale [31]. Ainsi, dans cette étude à gros effectif (étude nord-américaine portant sur 570 patients), 96 des 364 patients avec biopsies négatives (26 %) avaient soit une prostate histologiquement normale soit une HBP et ont été regroupés sous la rubrique no pathology.…”
Section: Le Test Urinaire Pca3 Dans Les éTats Pré-néoplasiques De La unclassified
“…Finalement, la meilleure explication d'un score PCA3 aussi bas dans l'HBP est que la prostate reste parfaitement saine. Cela est conforté par la démonstration, par plusieurs équipes, de l'absence de corrélation entre le score PCA3 et le volume prostatique [27,28,31,48].…”
Section: Le Test Urinaire Pca3 Dans Les éTats Pré-néoplasiques De La unclassified